- #1

DeadOriginal

- 274

- 1

$$

\sum\limits_{1}^{p-1}m^{k}\equiv -\epsilon_{k}(p) (\mod p).

$$

Proof: If ##(p-1)|k## then ##m^{k}\equiv 1## by Fermat's Theorem and

$$

\sum m^{k}\equiv p-1\equiv -1\equiv -\epsilon_{k}(p) (\mod p).

$$

If ##(p-1)\not|k## and ##g## is a primitive root of ##p## then ##g^{k}\not\equiv 1 (\mod p)##.

Everything makes sense so far, but then Hardy goes on to say:

The sets ##g,2g,...,(p-1)g## and ##1,2,...,p-1## are equivalent (mod p).

I don't see how these two sets are equivalent. I believe these two sets are residues but I am very confused about what residues are in general and so I cannot understand what Hardy means when he says that the two sets are equivalent. Any help to understand the last statement that Hardy makes or just any conversation about residues in general to help me understand them better would be greatly appreciated. Thanks!